Multiscale cytometry and regulation of 3D cell cultures on a chip - Sébastien Sart (Nature Portfolio, 2017)
3D cell culture is more relevant than the two-dimensional format, but methods for parallel analysis and temporal regulation of the microenvironment are limited. Here the authors develop a droplet microfluidics system to perform long-term culture of 3D spheroids, enabling multiscale cytometry of individual cells within the spheroid.